Service innovation and its impact: What do we know about? - Susanne Durst; Anne-Laure Mention; Petro Poutanen (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2015)
Despite the growing body of literature concentrating on service innovation, empirical research focusing on measuring its impact, mainly at firm-level, remains scarce. Adopting the perspective that the ability to monitor the service innovation process and to assess its impact is a pre-condition to properly manage it, we conduct a literature review of recent empirical studies on the measurement of service innovation to ascertain our current body of knowledge. We restrict our review to the period covering 2006 to 2014, as previous research has been extensively covered by Adams, Bessant, and Phelps (2006) and concentrate on published empirical academic articles which clearly examine 'service innovation' and its impact on performance. Relying on several inclusion and exclusion criteria, thirteen empirical studies were retained and are discussed in this paper. Although this study does not claim to be exhaustive, it shows that knowledge on the relationship between service innovation and performance is limited and that this area of research deserves further scrutiny. We conclude with some avenues for further research, in view of stimulating more research in this promising yet emerging field.
Keywords: M10; O30; O39; 330; Service innovation; Innovation management; Impact; Measurement; Literature review